Acquirer Returns When the Target is Privately Held, Listing Effect and Methods of Payment : Evidence from the Swedish, Norwegian, and Finnish M&A Market - Lassila, Niko (My University, 2024)
This thesis examines the abnormal returns associated with acquisition announcements, focusing on the target’s listing status and the methods of payment. The aim is to determine whether the phenomena reported in the U.S., U.K., and Western Europe are also applicable in Sweden, Norway, and Finland. The study first evaluates the applicability of the listing effect, which refers to the differences in acquirer returns between acquisitions of publicly listed and privately held targets. Building on this, the research delves deeper into the acquirer's abnormal returns when the target is privately held, examining stock and cash offers separately. The empirical analysis is conducted as an event study, estimating abnormal returns across four different event windows. The dataset consists of 388 acquisitions made by companies publicly listed in Sweden, Norway, or Finland. The main findings of this study reveal a statistically significant bidder cumulative abnormal return (CAR) of 1.61% when the target is privately held, compared to a statistically insignificant bidder CAR of 0.18% when the target is publicly listed, consistent with the listing effect. Furthermore, when the target is privately held, acquirers achieve higher significant CARs in stock offers (4.14%) than in cash offers (0.96%), aligning with the monitoring and information effects. Thus, the phenomena related to acquirer abnormal returns when acquiring privately held targets, as reported in the U.S., U.K., and Western Europe, are also applicable to the Swedish, Norwegian, and Finnish M&A market.

Tämä tutkielma tarkastelee yrityskauppailmoituksiin liittyviä epänormaaleja tuottoja keskittyen kohdeyhtiöiden listautumisstatukseen ja kaupan maksutapaan. Tarkoituksena on selvittää toteutuvatko Yhdysvalloissa, Isossa-Britanniassa ja Länsi-Euroopassa raportoidut ilmiöt myös Ruotsissa, Norjassa ja Suomessa. Tutkimus arvioi ensin ”listautumisvaikutuksen” soveltuvuutta. ”Listautumisvaikutuksella” viitataan tarjouksentekijöiden epänormaalien tuottojen eroavaisuuksiin listattujen ja listaamattomien kohdeyhtiöiden yritysostojen välillä. Tämän jälkeen analyysi syventyy tarjouksentekijän epänormaaleihin tuottoihin silloin, kun kohdeyhtiö on listaamaton, tarkastellen erikseen osake- ja käteistarjouksia. Empiirinen analyysi toteutetaan tapahtumatutkimuksena, jossa epänormaaleja tuottoja arvioidaan neljän eri tapahtumaikkunan yli. Tutkimusaineisto koostuu 388 yritysostosta, joissa tarjouksentekijä on Ruotsissa, Norjassa tai Suomessa listattu yritys. Tutkimuksen tulokset osoittavat 1,61% tilastollisesti merkitsevän kumulatiivisen epänormaalin tuoton (CAR:in) kun kohdeyhtiö on listaamaton, verrattuna tilastollisesti ei-merkitsevään 0,18% CAR:iin, kun kohdeyhtiö on listattu, mikä on linjassa ”listautumisvaikutuksen” kanssa. Lisäksi, kun kohdeyhtiö on listaamaton, tarjouksentekijät saavuttavat selvästi korkeammat tilastollisesti merkitsevät CAR:it osaketarjouksissa (4,14%) verrattuna käteistarjouksiin (0,96%), mikä on linjassa monitorointi- ja informaatioefektien kanssa. Näin ollen tarjouksentekijän epänormaaleihin tuottoihin liittyvät ilmiöt, jotka on raportoitu Yhdysvalloissa, Isossa-Britanniassa ja Länsi-Euroopassa, pätevät myös Ruotsin, Norjan ja Suomen yrityskauppamarkkinalla.
Keywords: Acquisitions, Payment Method, Abnormal Returns, yritysostot, maksutapa, epänormaalit tuotot